Renewable electrical energy sources in northern and southern region of India:-an overview of installation, potential and initiatives - Gantayat, Abhisek; Kant, Kamal; Santi Behera, Dr (International Journal of Engineering and Technology, 2018)
This paper highlights different literature surveys conducted by the authors and results indicates that the present scenario of unconven-tional energy sources in India. It is surveyed through various literatures and reported region wise; North and South of India [1]. The poten-tial and installed capacity of various unconventional energy is presented [1-2]. This research work is very much useful to go for the uncon-ventional sources of electricity as it is an alarming situation for the environment if we continue to use the conventional sources of energy. The unused sources of electrical energy can be taken up seriously and more research work in this field can help the world to progress to-wards a direction of free of global warming and ozone layer to be at safe zone. The tariff of solar plant is also reviewed year wise from 2010 -2016.Â